Perceived Stress and Adherence to the Dietary Recommendations and Blood Glucose Levels in Type 1 Diabetes - Aila J. Ahola; Carol Forsblom; Valma Harjutsalo; Per-Henrik Groop (Journal of Diabetes Research)
Stress may negatively impact self-management of diabetes and thereby deteriorate glycaemic control. Eating is the most frequently reported stress-release method. In this study, we investigated the association between perceived stress (PS), dietary adherence, and glycaemic control. Data from participants in the FinnDiane Study with type 1 diabetes who had completed a diet questionnaire and Cohen’s perceived stress scale (PSS) were included. In addition to using a continuous PSS score, participants were divided into three groups based on the PSS scores: the first PSS quartile, low levels of PS; second and third quartiles, moderate levels of PS; and fourth quartile, high levels of PS. A diet score reflecting the level of adherence to dietary recommendations was calculated. Analyses were conducted in the whole sample and in subgroups divided by body mass index (BMI<25 kg/m2 vs. BMI≥25 kg/m2). In the whole sample, high PS and continuous stress score were negatively associated with the diet score and with adherence to fish, fresh vegetable, low-fat liquid milk product, and vegetable oil-based cooking fat recommendations. The stress score was negatively associated with the diet score both in lean and in those overweight or obese. However, fish and fresh vegetable recommendations were only affected in those with corpulence. PS was not associated with mean blood glucose concentrations in the whole sample. When divided by BMI status, worse glycaemic control was observed in lean subjects reporting stress. In individuals with overweight or obesity, instead, high glucose concentrations were observed regardless of the level of perceived stress. Interventions to improve stress management could improve dietary adherence and glycaemic control and could thereby have the potential to improve long-term health and well-being of individuals with type 1 diabetes.